ANALYSIS OF DETERMINING THE WALKABILITY INDEX IN EDUCATIONAL AREA - Tinumbia, Nuryani; Rachmawati, Nia; Andreas, Azaria; Meutia, Wita; Putri, Aulia Salsabila; Fernando, Bryan Ezra (Jurnal Infrastruktur, 2024)
The educational area like campus is one of the urban areas that generate or attract pedestrian movements. Providing pedestrian facilities in this area is crucial and needs to be noticed by relevant stakeholders. The objective of this study is to assess pedestrian facilities in the Universitas Pancasila Campus area by applying the Walkability Index methodology. Primary data consists of pedestrian facilities inventory data inventory data and walkability assessments through field surveys, pedestrian perception data through distributing questionnaires by online. It is intended that this study will give any recommendation, particularly with enhancing the neighbourhood around the campus for pedestrians. The Walkability Index results for the Universitas Pancasila campus area show that all surveyed routes are in the quite good (average index value of 54.38), this means that the provision of pedestrian facilities in this campus area is quite adequate. The campus needs to focus on three characteristics going forward: the availability of crossing facilities, facilities for the disabled, and supporting facilities, according to the parameter score that was achieved.